Home range dynamics of spotted grunter, pomadasys commersonnii, in a South African intermittently open estuary - O'Connell, Bronwyn Anne (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2008)
The spotted grunter (Pomadasys commersonnii) is an important, estuarine-dependent, fishery species in southern Africa. Since estuaries are essential habitats in the life history of this species, the quantification of area use patterns and movements is important for fisheries management. In this study, acoustic telemetry was used to investigate movements, use of habitat and home range dynamics of spotted grunter in the small intermittently open East Kleinemonde Estuary on the Eastern Cape coast of South Africa. Nine spotted grunter (range: 326-489mm TL) were surgically equipped with uniquely coded acoustic transmitters. Positional fixes were obtained by manual tracking tagged individuals on six days and six nights during five tracking sessions from March to November 2004. In addition, five stationary data-logging receivers, moored at specific locations from the mouth to the top of the estuary provided additional long-term monitoring. Kernel home ranges (95% UD) varied in size (26 296-165 321mÂ²) but were all located in a common high use area situated between 300-1 300m from the estuary mouth, which coincided with the highest abundance of prey items. There was no significant variation in home range size [CÂ² (N = 9, df = 4) = 4.18; p = 0.38] between the temporally segregated tracking sessions (over nine months). The persistence of these home range estimates were confirmed by the long-term data-logging receivers. There was no significant diel variation in home range size [F(4, 64) = 0.05, p = 0.99] or core area size [F(4, 64) = 1.40, p = 0.25]. Fish length showed negative, although not significant, relationships between home range size (p = 0.225); number of home range areas (p = 0.065); core area size (p = 0.512) and home range length (p = 0.320). Use of habitat and home range dynamics of spotted grunter in the East Kleinemonde Estuary were consistent over the nine month study period, and they appeared to be influenced more by biotic than abiotic factors. However, when the mouth opened at the end of the study, most tagged fish vacated their home ranges and emigrated to sea.
Keywords: Grunts (Fishes) -- South Africa -- Eastern Cape; Pomadasys -- South Africa -- Eastern Cape; Estuaries -- South Africa -- Eastern Cape; Estuarine fishes -- South Africa -- Eastern Cape; Estuarine fishes -- Habitat -- South Africa -- Eastern Cape; Fishery management -- South Africa -- Eastern Cape; Fishes -- Home range; Fishes -- Home range -- South Africa -- Eastern Cape